Review of enterprise risk management (ERM) literature - Haji Togok, S.; Isa, C.R.; Zainuddin, S. (2014)
After series of both natural and man-made catastrophic events in the start of the 21st century, such as the earthquake in Japan and the recent crisis in the Eurozone, a trend to consolidate risk management policies, termed as Enterprise Risk Management (ERM), is seen in enterprises around the globe. Since then, ERM has been the subject of interest among business practitioners and academics. In general, the current article aims to critically review the existing literature on ERM published to date. Specifically, this paper seeks to provide an overview of the themes in existing ERM literature and offer direction for future research